Spatiotemporal persistence of multiple, diverse clades and toxins of Corynebacterium diphtheriae - Will, RC; Ramamurthy, T; Sharma, NC; Veeraraghavan, B; Sangal, L; Haldar, P; Pragasam, AK; Vasudevan, K; Kumar, D; Das, B; Heinz, E; Melnikov, V; et al. (Springer Nature, 2021)
Diphtheria is a respiratory disease caused by the bacterium Corynebacterium diphtheriae. Although the development of a toxin-based vaccine in the 1930s has allowed a high level of control over the disease, cases have increased in recent years. Here, we describe the genomic variation of 502 C. diphtheriae isolates across 16 countries and territories over 122 years. We generate a core gene phylogeny and determine the presence of antimicrobial resistance genes and variation within the tox gene of 291 tox+ isolates. Numerous, highly diverse clusters of C. diphtheriae are observed across the phylogeny, each containing isolates from multiple countries, regions and time of isolation. The number of antimicrobial resistance genes, as well as the breadth of antibiotic resistance, is substantially greater in the last decade than ever before. We identified and analysed 18 tox gene variants, with mutations estimated to be of medium to high structural impact.